Solução nutritiva salina enriquecida com nitrato de potássio no cultivo da alface crespa em sistema semi-hidropônico - Régis, Lúcia Regina de Lima (Universidade Federal Rural do Semi-Árido, 2018)
Lettuce is the most cultivated and adapted vegetable to hydroponic system. Quality of water used in nutritive solution requires attention as saline stress may reduce development and crop yield. This way, we must study alternatives to inhibit or reduce saline effects on plants. Due to scarcity of studies on saline stress and mineral nutrition in lettuce, this study aimed to evaluate the effect of enrichment of nutritive solution with potassium on semi-hydroponic growth of lettuce. The experiment was conducted in greenhouse at Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró-RN. Randomized blocks experimental design was used, with five treatments and four replicates. Treatments were represented by five nutritive solutions (S1 – standard solution; S2 – standard solution + NaCl (3.5 dS m-1); S3 – standard solution + NaCl (3.5 dS m-1) + KNO3 (50%); S4 – standard solution + NaCl (3.5 dS m-1) + KNO3 (100%); S5 – standard solution + NaCl (3.5 dS m-1) + KNO3 (150%). Plants water collected at 30 days after transplanting and evaluated for the following variables: amount of leaves (total and commercial), foliar area, stem diameter, stem length, fresh matter (total and commercial), total dry matter, foliar succulence, and specific foliar area. Results showed that the use of saline water in nutritive solution promotes reduction on plant growth, but enrichment with 100% of KNO3 in standard solution (S4) was efficient in reducing deleterious effect of saline stress on lettuce cultivated in coconut fiber.
Monografia
Keywords: Lactuca sativa; Hidropônico; Estresse salino; Potássio; Lactuca sativa; Hydroponic; Saline stress; Potassium; CIENCIAS AGRARIAS::AGRONOMIA